A novel application of queueing theory on the Caulerpenyne secreted by invasive Caulerpa taxifolia (Vahl) C.Agardh (Ulvophyceae, Caulerpales): a preliminary study - KANDEMIR-CAVAS, C.; CAVAS, L.; BAKI YOKES, M.; HLYNKA, M.; SCHELL, R.; YURDAKOC, K. (Mediterranean Marine Science, 2008)
Aquarium originated marine green alga Caulerpa taxifolia was introduced into the Mediterranean Sea accidentally in 1984. This invasion has been negatively affecting the sub-littoral ecosystem of the Mediterranean. One of the important reasons for its success in the Mediterranean is its secondary toxic metabolite called caulerpenyne (CPN). Furthermore, CPN has anti-proliferative and apoptotic activities, therefore, CPN can be considered as a potential native source in cancer therapy. For that reason, modeling this metabolite might be of importance. Increase and decrease of the CPN level before reaching the critical level can be expressed by means of a queueing system in which the number of ‘customers’ increases and decreases. In fact, production of CPN shows fluctuations for many environmental reasons, which allow us to apply queueing theory. In the present study, the expected time to reach the maximum caulerpenyne level was analyzed and evaluated using queueing theory.